Correlation Between Blood Glucose Fluctuations and Osteoporosis in Type 2 Diabetes Mellitus - Fuhua Chen; Ping Wang; Fang Dai; Qiu Zhang; Ruixue Ying; Liya Ai; Yiqing Chen (International Journal of Endocrinology)
The purpose of this review is to investigate the impacts of blood glucose fluctuations on diabetic osteoporosis, a complication of Type 2 diabetes mellitus (T2DM) that remains poorly understood. We reviewed the current evidence of the relationship between blood glucose fluctuations and diabetic osteoporosis in patients with T2DM. The findings indicate that blood glucose fluctuations may contribute to inhibiting the processes of bone formation and resorption, promoting diabetic osteoporosis and fractures in T2DM. Mechanistic studies, both in vitro and in vivo, reveal that these effects are largely mediated by oxidative stress, advanced glycation end products, inflammatory mediators, and multiple pathways inducing cell apoptosis or autophagy. Thus, maintaining the long-term stability of blood glucose levels emerges as a target to be pursued in clinical practice in order to safely reduce mean blood glucose and for its direct effects on osteoporosis and fractures in T2DM.